Metal immobilization and nitrate reduction in a contaminated soil amended with zero-valent iron (Fe0) - Houben, David; Sonnet, Philippe (Ecotoxicology and environmental safety, 2020)
Technologies based on zero-valent iron (Fe0) are increasingly being used to immobilize metals in soils and remove metals and nitrate from waters. However, the impact of nitrate reduction on metal immobilization in metal contaminated soils has been poorly investigated so far. Here, different concentrations of Fe0 filings (1%, 2% and 5%; wt%) were applied to a metal contaminated soil. The resulting nitrate reduction and metal (Cd and Zn) immobilization was investigated using a column leaching experiment for 12 weeks. Corrosion of Fe0 filings and precipitation of Fe oxyhydroxydes (FeOOH) on the surfaces of the filings were observed using SEM-EDS and EMPA-WDS at the end of the experiment. Compared to the untreated soil, total nitrate amounts released were lowered by 47%, 59% and 87% in the presence of 1%, 2% and 5% of Fe0, respectively. Concomitantly with nitrate reduction, Cd and Zn concentrations in leachates were strongly alleviated in the presence of Fe0, which was partly attributed to the rise of soil pH subsequent to nitrate reduction. More importantly, biotests with Lupinus albus L. revealed that the mechanisms involved in metal immobilization are stable to root-induced acidification. However, Fe0 was not efficient to reduce Cd concentration in Lolium multiflorum Lam., indicating that root processes other than acidification may re-mobilize metals. •Nitrate reduction and metal immobilization was studied in a soil amended with Fe0.•Corrosion of Fe0 filings formed a surface layer of Fe oxyhydroxides.•The application of Fe0 immobilized strongly and rapidly metals.•pH increase subsequent to nitrate reduction improved metal immobilization.•Immobilization mechanisms were stable under root-induced acidification.